Answer:
-(8/-4)² + 2 - 4³ = -66
Explanation:
-(8/-4)² + 2 - 4³
Here we need to respect the order of operations.
So ,first we calculate what’s between parentheses :
8/-4 = -2
Then
-(8/-4)² + 2 - 4³ = -(-2)² + 2 - 4³
Then
We calculate the exponent :
(-2)² = (-2) × (-2) = 4
4³ = 4 × 4 × 4 = 64
Then
-(8/-4)² + 2 - 4³ = -4 + 2 - 64
Then
The expression -4 + 2 - 64 contains addition and subtraction.
So ,we start calculating from left to right :
-4 + 2 = -2
Then
-4 + 2 - 64 = -2 - 64 = -66
Conclusion :
-(8/-4)² + 2 - 4³ = -66